The Bundle Theory of Particulars and Accidental Properties - Nakoneczny, Michał (Filozofia Nauki, 2014)
In this paper I evaluate four arguments formulated against the Bundle Theory of Particulars: the argument from tautologous subject-predicate discourse, the argument from essentialism, the argument from the impossibility of diachronic change, and the argument from the Principle of Identity of Indiscernibles. I propose a general strategy to deal with those and structurally similar problems and show how this strategy solves the four objections. The offered solution consists in analysing subject-predicate discourse in terms of coexemplification of properties rather than set-inclusion and in postulating that ordinary particulars are not bundles of properties but bundles of higher-order: either bundles of temporal parts (that are bundles of properties), which allows us to escape the problem of impossibility of change over time; or bundles of modal parts, which enables us to refute the argument from essentialism; or bundles of modal parts that are bundles of temporal parts that are bundles of tropes - which clears up both difficulties.